Pengaruh Keselamatan dan Kesehatan Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT X Jakarta - Ryan Pratama; Rani Kurniasari (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This study aims to determine the effect of Occupational Safety and Health and the Work Environment on Employees at PT X. The method used in this research is a quantitative approach in measuring the effect of occupational safety and health and the work environment on employee performance at PT X Jakarta. The sample technique used in this study was a saturated sample technique with a total of 35 employees. Data collection methods using observation, questionnaires and case studies. The data analysis method uses validity test, reliability test, coefficient of determination, classical assumption test and hypothesis testing using SPSS Version 25. The results of this study indicate that the t value of occupational safety and health has a negative and insignificant effect on employee performance of (-1.433<1.694) and sig value. 0.161>0.05 and the work environment has a positive effect and has a positive impact on employee performance (4.557<1.694) and sig value. 0.000<0.05. Simultaneously, the value of F (22.487>3.28) and sig value. 0.000 <0.05 and the coefficient of determination of 0.584, it can be concluded that occupational safety and health (X1) and the work environment (X2) together have an influence of 58.4% on employee performance (Y)